Does an increase in working hours affect mortality risk? The relationship between working hours and mortality among the older population - Mercan, Murat A.; Barlin, Hande; Begen, Nazire (SAGE PUBLICATIONS INC, 2022)
BACKGROUND: Population aging, caused by an increase in life expectancy and decrease in fertility rates, has created changes and challenges in various spheres, including the labor market. Though health deteriorates with age, more and more older adults choose to stay in the labor force and work into late life. OBJECTIVE: Understanding the effects of various work conditions on the health of older workers is crucial for designing policies and interventions to ensure healthy late life and maintain a productive workforce. To contribute to this endeavor, this study investigates the relationship between long working hours (LWH) and mortality among older populations. METHODS: The study uses the Cox proportional hazards regression model to investigate data from the Health and Retirement Survey (HRS) between the years 1992-2016, a longitudinal nationally representative dataset from the United States. RESULTS: The results indicate that working 50 hours or more per week is not associated with an increased risk of mortality, for the full sample (1.45 [95% CI: 0.86, 2.45]), for both genders (females 0.51 [95% CI: 0.06, 4.28], males 1.45 [95% CI: 0.81, 2.61]), and for immigrants (female immigrants 0.55 [95% CI: 0.06, 4.75], male immigrants 1.44 [95% CI: 0.79, 2.62]). CONCLUSIONS: This analysis confirms and extends the findings of earlier studies by taking into consideration the potential impact of many demographic, socioeconomic, work-related and health-related factors.
Keywords: Immigrants; population aging; work conditions; CORONARY-HEART-DISEASE; UNITED-STATES; HEALTH-STATUS; WHITEHALL-II; UNPUBLISHED DATA; SOCIAL-SECURITY; ADULT MORTALITY; OVERTIME WORK; IMMIGRANT; BEHAVIORS; Public, Environmental & Occupational Health